Use of Artificial Cell Microcapsule Containing Thalidomide for Treating TNBS-induced Crohn's Disease in Mice - Fakhoury, M.; Coussa-Charley, M.; Al-Salami, Hani; Kahouli, I.; Prakash, S. (Bentham Science Publishers, 2014)
In this study, we examined the in-vivo characteristics of a novel microencapsulated thalidomide formulation in a murine model of experimental Crohn's disease. Crohn's disease was induced with a single intra-colonic injection of 120 mg/kg of bodyweight of 2,5,6-trinitrobenzene sulfonic acid (TNBS) dissolved in 30% ethanol in Balb/c mice. Level of tumor necrosis factor alpha (TNF-), interleukin one beta (IL-1), interleukin 6 (IL-6) and nitric oxide (NO) were measured in tissue homogenate. Moreover, myeloperoxidase (MPO) activity was determined to assess the extent of neutrophil infiltration. Dose response study showed that treating the mice with microencapsulated thalidomide (100 mg/kg of bodyweight) for two weeks significantly decreased the degree of intestinal inflammation related to Crohn’s disease. Higher and lower doses (0, 25, 50 and 200 mg/kg of bodyweight) did not exhibit comparable effects. The present study validates the success of alginate-poly-L-lysine-alginate (APA) microcapsules containing thalidomide in reducing colonic inflammation, and proposes a potential remedy for Crohn’s disease.